TEACHING OBSTETRICS AND GYNAECOLOGY TO MALE UNDERGRADUATE MEDICAL STUDENTS: STUDENT’S PERCEPTION - Alam, Kinza; Safdar, Chaudhry Aqeel; Munir, Tahir Ahmad; Ghani, Zeeshan (Journal of Ayub Medical College Abbottabad, 2014)
Background: In Pakistan there is a dearth of male practitioners in obstetrics and gynaecology (ObG) to cater for emergent needs. The Study was done to explore views of male medical students towards ObG as part of curriculum and to identify the problems during clerkship and its impact on selection of ObG as career. Methods: The study used a 20-item questionnaire-based survey at Shifa College of Medicine from November 2010 to December 2011. Third and fourth year male students (n=124) who completed ObG rotation were the participants. Inquiries were made regarding patient doctor interaction under residents and faculty members, perception of gender-bias during clerkship, inclusion of ObG in curriculum and subsequently as career. Results were analyzed using binary regression analysis. Results: Sixty percent students were satisfied though embarrassed and under pressure during gynaecological examination in consultant supervision. Another 61% said that ObG should be a part of curriculum (p-0.013) and necessary for male students (p-0.008). 62% of the respondents were of the view that faculty has a major role in encouraging the students to take up ObG as career. 84% students replied in negative to adopt it as profession (p 0.002). Conclusion: Although basic obstetric curricular objectives are important for medical practitioners, our social set up discourages male students to have concrete clinical interaction. The faculty needs to take a special supportive role to encourage learning and motivation for this specialty. Keywords: Obstetrics and Gynaecology, career choice, Gender bias, medical students